The Impact of Leadership Longevity on Innovation in a Religious Organization - Fritz, David A. (Journal of business ethics, 2010)
Navigating organizations through a chang- ing environment is central to leadership. Thus, innovativeness has proven to be critical to the process of achieving strategic competitiveness (Yukl, Leadership in Organizations, 1998). This skill is particularly needed when the firm is confronted with the unique challenges of a religious organization. The existence of innovation and the depen- dencies that encourage or restrict its existence in this environment are largely unknown. Utilizing a sample of 250 religious organizations in five geographical areas this research explores the impact of the leader tenure on the degree of organizational innovation. An analysis of variance for innovative strategy use across the three tenure groups was significant, F (2, 247) = 6.08, p < 0.01, which indicated innovation differences across the three levels of leader tenure. Post hoc analysis indicated that the low tenure leadership group was associated with lower levels of innovation than either of the other groups. Detailed findings are presented and the managerial implications and suggestions are provided. This research has strong implications for implementation of leadership development and strategic management of the increasing number of socially conscious organizations and organizations with large volunteer components.